A bilateral SPCN is elicited by to‐be‐memorized visual stimuli displayed along the vertical midline. (22nd March 2022) - Chen, Yanzhang; Brigadoi, Sabrina; Schiano Lomoriello, Arianna; Jolicœur, Pierre; Simal, Amour; Fu, Shimin; Baro, Valentina; Dell'Acqua, Roberto
Abstract: We recently showed that deploying attention to target stimuli displayed along the vertical meridian elicits a bilateral N2pc, that we labeled N2pcb ( Psychophysiology ). Here we investigated whether a different component, the sustained posterior contralateral negativity (SPCN), shows the same property when a varying number of visual stimuli are displayed either laterally or on the vertical meridian. We displayed one or two cues that designated candidate targets to be detected in a search array that was displayed after a retention interval. The cues were either on the horizontal meridian or on the vertical meridian. When the cues were on the horizontal meridian, we observed an N2pc followed by an SPCN in their classic form, as negativity increments contralateral to the cues. As expected, SPCN amplitude was greater when two cues had to be memorized than when only one cue had to be memorized. When the cues were on the vertical meridian, we observed an N2pcb followed by a bilateral SPCN (or SPCNb). Critically, like SPCN, SPCNb amplitude was greater when two cues had to be memorized than when only one cue had to be memorized. A series of additional parametrical and topographical comparisons between N2pcb and SPCNb revealed similarities but also some important differences between these two components that we interpreted as evidence for their distinct neural sources. Abstract : We challenge the view that the SPCN ERP component cannot track the memory maintenance of objects displayed along the vertical meridian. Owing to the receptive fields of posterior neurons straddling on the intersection of the two visual hemifields, bilateral N2pc (N2pcb) and SPCN (SPCNb) activity can be detected using a cued visual search design.